Rural Surgical Training in the United States: Delineating Essential Components Within Existing Programs. Issue 11 (November 2020) - Rossi, Isolina; Rossi, Matthew; Mclaughlin, Emily; Minor, Derek; Smithson, Lauren; Borgstrom, David; Sarap, Michael; Deveney, Karen
Background: Rural access to surgical care has reached crisis level. Practicing in rural America offers unique challenges with limited resources and specialists. Most training programs do not provide enough exposure to the endoscopic or the surgical subspecialty skills to prepare a resident for an isolated rural environment. As awareness has increased, many programs have modified curriculum to address this need. The Advisory Council on Rural Surgery (ACRS) of the American College of Surgeons set out to delineate important components of rural training programs and measure to what degree the existing heterogeneous programs contain these components. Study Design: The ACRS identified 4 essential components of rural surgical training based on literature and expert opinion. These components included rotations in a rural setting, broad exposure to surgical specialties, endoscopy experience, and lack of competing specialty learners. A list of Accreditation Council for Graduate Medical Education programs from a prior publication was updated with the 2019 Fellowship and Residency Electronic Interactive Database self-identified "rural track" programs, reviewed, and categorized. Results: We identified 39 programs that self-identified as having a rural emphasis. Depending on the extent of which 4 essential components were included, programs were categorized as either "Broad" (12 programs), "Basic" (20 programs), or "Indeterminate" (7 programs). Conclusion: The ACRS described the optimal components of a rural surgical training program and identified which components are present in those surgical residencies which self-identified as having a rural focus. This information is valuable to students planning a future in rural surgery and benefits programs hoping to enhance their curriculum to meet this critical need.